Study on the determinants of health professionals’ performance on diabetes management care in China - Shanshan Jing; Yahang Yu; Beibei Yuan (BMC Primary Care, 2023)
Abstract Background As the direct providers of diabetes management care in primary health care facilities (PHFs) in China, health professionals’ performance on management care of diabetes determines the quality of services and patients’ outcomes. This study aims to analyze the key determinants of health professionals’ performance on diabetes management care in PHFs in China. Methods We conducted a cross-sectional study in 72 PHFs in 6 cities that piloted the contracted family doctor service (CFDS). Self-developed questionnaire was used to measure three kinds of factors (capacity, motivation and opportunity) potentially influencing the performance of health professionals. The performance of diabetes management care in the study was measured as whether health professionals delivered 7 service items required by the National Basic Public Health Service Guideline with a total of 7 points and was divided into three grades of good, medium and bad. The questionnaire is self-administered by all the health professionals involved in the study with the number of 434. The Chi-square tests were used to compare differences of performance on diabetes management care among health professionals with different characteristics. The ordinal logistic regression was used to analyze the determinants on the performance of diabetes management care. Results Health professionals who got higher score on diabetes knowledge test had odds of better performance on diabetes management care (OR = 1.529, P < 0.001). health professionals with higher degree of self-reported satisfaction on training (OR = 1.224, P < 0.05) and perception of decreasing workload (OR = 3.336, P < 0.01) had odds of better performance on diabetes management care. While health professionals with negative feeling on information system support had odds of worse performance on diabetes management care (OR = 0.664, P < 0.01). Conclusions Attention should be paid to the training of health professionals’ knowledge on diabetes management capacity. Furthermore, measures to improve training for health professionals could satisfying their needs for self-growth and improve the motivation of health professionals. The information system supporting management care should be improved continuously to improve the health professionals’ working opportunities and decrease the workload.